The impact of tuberculosis-induced hyperglycemia on pulmonary microbiota and airway mucus secretion in individuals not previously diabetic: A systematic review and meta-analysis protocol - Victor Moses Musyoki; Marianne Mureithi; Annamari Heikinheimo; Elizabeth Maleche-Obimbo; Kariuki Njaanake; Omu Anzala (PLoS ONE, 2025)
The lung environment harbours a community of microbes that play a significant role in health and disease, including innate protection against pathogenic microorganisms. Infection with Mycobacterium tuberculosis, psychological stress associated with the tuberculosis (TB) disease, and the metabolites from the rifampicin treatment regimen have been reported to induce hyperglycemia and consequently type 2 diabetes mellitus (T2DM) in individuals not previously diabetic. The high glucose concentration is proposed to alter the composition of the lung microbiota and airway homeostasis, exerting an influence on TB disease and treatment outcomes. In this systematic review, we propose to synthesize literature on TB-induced hyperglycemia and its impact on lung microbiota and secretion of airway mucus in individuals not previously diabetic. A systematic search will be carried out on PubMed, EMBASE, MEDLINE, PROQUEST, Cochrane, SCOPUS, and manually on Google Scholar and references of relevant articles to identify other studies. We will review published articles that include studies on TB-induced hyperglycemia, pulmonary microbiome, mucin secretion, and (or) airway surface liquid upon TB diagnosis and during treatment. The quality of the study articles will be assessed using the modified Newcastle-Ottawa Scale (NOS). Meta-analysis will be conducted using random effect model for heterogeneity to pool estimates on microbial diversity. Egger’s test will be performed to explore any selective reporting bias. The findings of the systematic review and the meta-analysis will be reported as per the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) protocol guidelines. This protocol was developed and uploaded onto the International Prospective Register of Systematic Reviews (PROSPERO) database, registration number: CRD42024482248.